Case report: canine splenic blastomycosis - Palacios Galvis, Andrés Felipe (2019)
The aim of this report was to describe six cases of canine splenic blastomycosis between 2013 and 2017 in two pathology laboratories in Bogotá, Colombia (Anatomopathology Laboratory of the University of La Salle-Bogotá, pathology laboratory of CORPAVET©). The samples were obtained by splenectomy consistent with the suspicion of neoplastic disease. The pathological diagnoses were considered as accidental findings of fungal splenitis caused by Blastomyces spores, as there was no clinical or laboratory evidence of joint systemic disease.